ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI ARITMETIKA SOSIAL BERBASIS JUMPING TASK DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT - Evy Alvionita Laurita, Shofia; Hobri, H; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2018)
This study described about the creative thinking ability of the students in SMP Negeri 8 Jember on social arithmetic material based on Jumping Task. The data collection method used were tests, observations and interviews. This study used a description question of social arithmetic material based on jumping task and Group Embadded Figure Test (GEFT) to determine the cognitive style of students. This study was conducted in grade VII G of SMP Negeri 8 Jember with the total number of student was 31. The test questions used use the indicators of creative thinking, they were fluency, flexibility and novelty. After the GEFT test and the creative thinking ability test were done, the research subjects were 6 students. Two students with high creative thinking ability with field dependent cognitive style, two students with moderate creative thinking ability with field dependent and field independent cognitive style, and two students with low field independent creative thinking ability. Keywords: Creative thinking, Group Embadded Figure Test (GEFT), Jumping Task.